Money Demand Stability and Inflation Prediction in the Four Largest EMU Countries - Kai Carstensen; Jan Hagen; Oliver Hossfeld; Abelardo Salazar Neaves (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2008)
In this paper we analyze the money demand functions of the four largest EMU countriesand of the four-country (EMU-4) aggregate. We identify reasonable and stable moneydemand relationships for Germany, France and Spain as well as the EMU-4 aggregate.For the case of Italy, results are less clear. From the estimated money demand functions,we derive both EMU-4 and country-specific measures of money overhang. We find thatthe EMU-4 overhang measure strongly correlates with the country-specific measures,particularly since the start of EMU, and is useful to predict country-specific inflation.However, it generally does not encompass country-specific money overhang measuresas predictors of inflation. Hence, aggregate money overhang is an important, but by farnot an exhaustive, indicator for the disaggregate level.
Keywords: E41; E52; 330; Money demand; stability; money overhang; inflation forecast; Geldnachfrage; Schätzung; Geldmenge; Monetärer Indikator; Inflation; Europäische Wirtschafts- und Währungsunion; Deutschland; Frankreich; Spanien; Italien